A subjetividade lírica em “Sonetos que não são” e “Cantares”, de Hilda Hilst - Souza, Sávio Pires de (2022)
Lyric poetry is considered a subjective genre that expresses through a self the reflections, emotions, personal feelings of the poet. However, this conception defended by Hegel and which is still present in the academic space undergoes some changes, since the 20th and 21st centuries are moments of transformation in terms of social, political, cultural and economic aspects, which implied aesthetic changes in the modern and contemporary art. Due to this context, it gives rise to a poetic expression focused on impersonality, depersonalization, multiplicity, the presence of multiple personalities, thus having lost identities, among others. In this way, Hilda Hilst, a writer from São Paulo, inserts herself in this environment of transformations and problematizes the situation of the lyrical subject, which manifests itself in her poems through a feminine discourse that opens space for a new awareness of women, not only in relation to her individuality, but its collectivity, for assuming a position that for a long time was not granted to her. Therefore, the general objective of this dissertation is to carry out a systematic study about the composition of the lyrical subject in the works Sonetos que não são (1959) and Cantares (2004).The methodology used for the research started from analyzes that allowed to discuss theoretical perspectives of who is and how a subject is constituted in the author's poetic productions. The studies undertaken made it possible to raise two important questions about the poetic subject that is established in the works: the unfolding of the self into a mask and the presence of a subject that is constituted from its relationship with the other. This trajectory culminated in the elaboration of three chapters, counting on Octavio Paz (1984), Hegel (1997), Combe (1999), Hamburguer (2007) and Bataille (2017) as part of the theoretical contribution, evidencing the constitution of a mobile, dynamic and, above all, plural subjectivity.